Microbiota and the control of blood-tissue barriers - Maha Al‐Asmakh; Lars O. Hedin (2015)
The gastro-intestinal tract is an ecosystem containing trillions of commensal bacteria living in symbiosis with the host. These microbiota modulate a variety of our physiological processes, including production of vitamins, absorption of nutrients and development of the immune system. One of their major functions is to fortify the intestinal barrier, thereby helping to prevent pathogens and harmful substances from crossing into the general circulation. Recently, effects of these microbiota on other blood-tissue barriers have also been reported. Here, we review the evidence indicating that gut bacteria play a role in regulating the blood-brain and blood-testis barriers. The underlying mechanisms include control of the expression of tight junction proteins by fermentation products such as butyrate, which also influences the activity of histone deacetylase.